2012
DOI: 10.1007/s11999-012-2255-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Dual Antibiotic Prophylaxis Better Prevent Surgical Site Infections in Total Joint Arthroplasty?

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 37 publications
6
68
1
2
Order By: Relevance
“…On the surface, this study appears to validate the concept that dual antibiotic regimen including vancomycin increases the risk of acute kidney injury. Additionally, a previous study of this series of patients has shown that the addition of vancomycin to the prophylactic antibiotic regimen did not result in less surgical site infections than cefazolin alone [6]. This was consistent with other studies [5,9].…”
Section: Where Do We Need To Go?supporting
confidence: 92%
See 1 more Smart Citation
“…On the surface, this study appears to validate the concept that dual antibiotic regimen including vancomycin increases the risk of acute kidney injury. Additionally, a previous study of this series of patients has shown that the addition of vancomycin to the prophylactic antibiotic regimen did not result in less surgical site infections than cefazolin alone [6]. This was consistent with other studies [5,9].…”
Section: Where Do We Need To Go?supporting
confidence: 92%
“…Moreover, Vancomycin needs to be combined with traditional prophylactic agents in order to provide coverage against Gram-negative bacteria. The benefits to adding vancomycin to prophylactic regimens is still hotly debated [5][6][7].…”
mentioning
confidence: 99%
“…Many prior studies have compared vancomycin with cephalosporins and have demonstrated conflicting results [11][12][13]16]. These studies are rarely focused on the blactam-allergic population and frequently represent the outcomes of universally administering vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Tyllianakis et al [16] demonstrated no difference (six of 188 versus six of 120) in the SSI or PJI rate between those receiving cefuroxime and vancomycin in a prospective randomized trial in nonpenicillin-allergic patients. Sewick et al [12] evaluated the use of dual antibiotics (vancomycin and cefazolin) with cefazolin monotherapy and found no difference in the infection rate (1.1% versus 1.4%; p = 0.64). In contrast, Ponce et al [11] revealed that vancomycin (2.3%) demonstrated an approximately two times higher rate of 30-day SSI than cefazolin (1.3%, adjusted OR 1.73) and clindamycin (1.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation